PENGETAHUAN MANAJEMEN TENTANG PEMAHAMAN PELANGGAN DAN PEGAWAI MENGENAI GREEN PRODUCT TERHADAP KUALITAS PRODUK YANG DIMODERASI OLEH AKUNTANSI LINGKUNGAN DAN KINERJA KUALITAS - Joko Susilo (Asian Journal of Innovation and Entrepreneurship, 2012)
This study intends to explore the effect of the management knowledge acquisition to customers and employees about environmentally friendly products on product quality. At a later stage, this study also analyzed whether the quality performance factor and the application of environmental accounting are moderating the relationship between management knowledge and product quality. Specific objectives of this study was to establish management's knowledge for customer understanding about green product will have an effect on product quality, to determine the distribution of management knowledge to the employees about the involvement of employees in the manufacturing of green product will have an effect on product quality, to establish quality performance moderate the relationship of knowledge management of customer and diistribusi knowledge to employees with quality products, and to establish environmental accounting reporting moderate the relationship of management knowledge to customers and knowledge distribution to employees with quality products. This study was designed in an exploration that examines the acquisition of management knowledge about customers and employees on product quality, as well as the moderating variable is the quality of performance and application of environmental accounting. Regression test done to prove the hypothesis set out in this study. A discovery in this study prove that the acquisition of management knowledge about customers and employees about green products affect the quality of environmentally friendly products. Variable quality of performance can also be proved empirically moderate the relationship. While the application of environmental accounting is not empirically proven to moderate the relationship of knowledge management and product quality.Keywords: green product, knowledge management, customers and employees, product quality